TACTICS, TECHNOLOGY, AND DEFENSE POLICY IN JOINT EXERCISES OF THE INDONESIAN AND RUSSIAN NAVIES - Sarjito, Aris (Jurnal Pertahanan dan Bela Negara, 2024)
The joint exercises between the Indonesian Navy (TNI AL) and the Russian Navy play a crucial role in shaping defense capabilities and policies within the Indo-Pacific’s evolving security landscape. As regional maritime security challenges grow, driven by threats such as piracy, illegal fishing, and geopolitical tensions, these exercises provide a strategic framework for enhancing operational interoperability and collective defense readiness. This research explores how the tactical and technological components of these exercises influence the defense strategies of both nations. Using a qualitative approach based on secondary data from government reports, defense journals, and academic publications, this study examines the impact of coordinated tactics, such as anti-submarine warfare and advanced communication systems, on operational efficiency and defense policy. Findings reveal that joint exercises improve real-time data sharing and surveillance capabilities, shaping Indonesia’s active neutrality and Russia’s strategic reach in Southeast Asia. These insights underscore the exercises’ role in fostering regional stability through enhanced collaboration. The conclusion highlights the alignment of defense policy and operational readiness, positioning both nations as key contributors to Indo-Pacific security.